Pemberantasan Tindak Pidana Korupsi Di Bandar Lampung Dalam Perspektif Psikologi Kriminal - Hasan, Zainudin; Musyafa, Hattal; Justicia, Ryan; Taufiqurahman; Aldiansyah (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2025)
This study aims to analyze the eradication of corruption in Bandar Lampung through the perspective of criminal psychology. Corruption is a serious problem that hinders development and harms society. This study identifies psychological factors that drive individuals to engage in corruption, including economic motivation, social pressure, and behavioral norms. With a qualitative approach, data were collected through interviews with law enforcement officers, psychologists, and the community. The results of the study indicate that understanding the psychological aspects of corruption perpetrators can increase the effectiveness of prevention and enforcement strategies. In addition, education and socialization about the negative impacts of corruption need to be improved to build public awareness. This study provides recommendations for legal policies in Bandar Lampung to integrate psychological approaches in efforts to eradicate corruption, including training for law enforcers and rehabilitation programs for perpetrators. Thus, it is hoped that efforts to eradicate corruption will not only focus on legal sanctions, but also on changing the behavior and mentality of society. This study contributes to the development of legal theory and practice as well as criminal psychology in the context of eradicating corruption in Indonesia.